Konjunkturbereinigung in der Schuldenbremse reformieren: Revisionen erst zeitverzögert einrechnen; Reforming cyclical adjustment in the debt brake - Jana Kremer; Jan Kuckuck; Karsten Wendorff (Wirtschaftsdienst, 2022)
– In this article, we point out requirements for potential output estimates used for cyclical adjustment in the German debt brake. Further, we propose supplementing the cyclical component in the debt break with an error term - regardless of the specific potential output estimation approach. The error term provides fiscal policy more time to adjust to potential output revisions and tax revenue forecast errors. Simulations based on past data show that the error term reduces erratic budgetary adjustments and strengthens automatic stabilisers.
Keywords: E62; H61; H68; 330